RETRACTED: Effect of Weekly Long-Acting Growth Hormone Replacement Therapy Compared to Daily Growth Hormone on Children With Short Stature: A Meta-Analysis - Ma, Liyan; Li, Liangyi; Pan, Wen; Huang, Congfu; Liu, Limei; Zhang, Xiaoxiao (Frontiers in Endocrinology, 2021)
Background We performed a meta-analysis to evaluate the efficacy and safety of weekly long-acting growth hormone replacement therapy compared to daily growth hormone in children with short stature. Methods A systematic literature search up to April 2021 was performed and 11 studies included 1,232 children with short stature treated with growth hormone replacement therapy at the start of the study; 737 of them were using weekly long-acting growth hormone replacement therapy and 495 were using daily growth hormone. They were reporting relationships between the efficacy and safety of long-acting growth hormone replacement therapy and daily growth hormone in children with short stature. We calculated the odds ratio (OR), and mean difference (MD) with 95% confidence intervals (CIs) to assess the efficacy and safety of weekly long-acting growth hormone replacement therapy compared to daily growth hormone in children with short stature using the dichotomous or continuous method with a random or fixed-effect model. Results Long-acting growth hormone replacement therapy had significantly lower height standard deviation scores chronological age (MD, −0.10; 95% CI, −0.13 to −0.08, p <0.001), and insulin-like growth factor binding protein-3 (MD, −0.69; 95% CI, −1.09 to −0.30, p <0.001) compared to daily growth hormone in children with short stature. However, growth hormone replacement therapy had no significantly difference in height velocity (MD, −0.09; 95% CI, −0.69–0.5, p = 0.76), height standard deviation scores bone age (MD, −0.04; 95% CI, −0.10–0.02, p = 0.16), insulin-like growth factor 1 standard deviation scores (MD, 0.26; 95% CI, −0.26–0.79, p = 0.33), and incidence of adverse events (OR, 1.16; 95% CI, 0.90–1.50, p = 0.25) compared to daily growth hormone in children with short stature. Conclusions Long-acting growth hormone replacement therapy had significantly lower height standard deviation scores chronological age, and insulin-like growth factor binding protein-3 compared to daily growth hormone in children with short stature. However, growth hormone replacement therapy had no significant difference in height velocity, height standard deviation scores bone age, insulin-like growth factor 1 standard deviation scores, and incidence of adverse events compared to daily growth hormone in children with short stature. Further studies are required to validate these findings.